The Effect of Masterbatch Recipes on the Homogenization Properties of Injection Molded Parts - László Zsíros; Dániel Török; József Gábor Kovács (International Journal of Polymer Science)
Appearance is a key factor in most injection molding applications. Unfortunately, there is no widespread method to objectively test visual appearance, such as color inhomogeneity of the parts or other surface defects. We developed an evaluation method to characterize the color inhomogeneity of injection molded parts. First, we examined manufacturing conditions and masterbatch recipes and then the individual effects of the components and their interactions on homogeneity.